Older multimorbid patients' experiences on integration of services: a systematic review - Lilian Keene Boye; Christian Backer Mogensen; Tine Mechlenborg; Frans Boch Waldorff; Pernille Tanggaard Andersen (BMC, 2019)
Abstract Background Half of the older persons in high-income counties are affected with multimorbidity and the prevalence increases with older age. To cope with both the complexity of multimorbidity and the ageing population health care systems needs to adapt to the aging population and improve the coordination of long-term services. The objectives of this review were to synthezise how older people with multimorbidity experiences integrations of health care services and to identify barriers towards continuity of care when multimorbid. Methods A systematic literature search was conducted in February 2018 by in Scopus, Embase, Cinahl, and Medline using the PRISMA guidelines. Inclusion criteria: studies exploring patients' point of view, ≥65 and multi-morbid. Quality assessment was conducted using COREQ. Thematic synthesis was done. Results Two thousand thirty studies were identified, with 75 studies eligible for full text, resulting in 9 included articles, of generally accepted quality. Integration of health care services was successful when the patients felt listened to on all the aspects of being individuals with multimorbidity and when they obtained help from a care coordinator to prioritize their appointments. However, they felt frustrated when they did not have easy access to their health providers, when they were not listened to, and when they felt they were discharged too early. These frustrations were also identified as barriers to continuity of care. Conclusions Health care systems needs to adapt to people with multimorbidity and find solutions on ways to create flexible systems that are able to help older patients with multimorbidity, meet their individual needs and their desire to be involved in decisions regarding their care. A Care coordinator may be a solution.